New clinical data and guidelines on menopausal hormone therapy since the Women’s Health Initiative study: route of administration and safety profile - Woźniakowska, Ewa; Milart, Paweł; Woźniak, Sławomir; Wrona, Wojciech; Szkodziak, Piotr; Paszkowski, Maciej; Czuczwar, Piotr; Paszkowski, Tomasz (Menopause Review/Przegląd Menopauzalny, 2013)
New data and guidelines on menopausal hormone therapy have become available since the publication of the Women’s Health Initiative study. This article is aimed to update information regarding the mmendations for the administration route and benefit-risk profile of menopausal hormone therapy. The clinical guidelines generally do not recommend any particular route as better than the others. Available data show that use of transdermal estradiol and micronized progesterone may reduce the risk of venous thromboembolism, breast cancer, stroke, and coronary heart disease.